The Effect of Organizational Commitment and Culture on Organizational Citizenship Behavior (OCB): A Case Study of Teacher at Muhammadiyah High School, Jember Regency (Universitas Muhammadiyah Jember, 2021)
Organizational Citizenship Behavior (OCB) plays an important role in increasing the creativity, effectiveness, and efficiency of an institution or organization. One indicator that can be used to see OCB behavior is employee commitment to the organization or institution where they work. In addition, organizational culture can also determine the success of creating OCB as a common consensus for organizational progress. This study aims to determine the effect of organizational commitment and culture on OCB in Muhammadiyah high school teachers in Jember Regency. The research approach used is a quantitative approach. The data source used in this study is primary data using Variance-based SEM or Partial Least Square (SEM-PLS) testing. Primary data was obtained from direct questionnaire answers from respondents which would be sent to all Muhammadiyah high school teachers in Jember Regency. Based on the results of the study indicate that there is work commitment and organizational culture have a significant and positive effect on OCB.